Pengaruh Komunikasi Efektif, Kepemimpinan, Disiplin Dan Semangat Kerja Terhadap Kinerja Pegawai - Viyeni, Maria Fitri Ayu Olin; Kirana, Kusuma Chandra; Septyarini, Epsilandri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The purpose of this study was to influence the effect of effective communication, leadership, discipline, and work enthusiasm on employee performance at the Desa Nggorang di Kecamatan Komodo Kabupaten Manggarai Barat. This study used a saturated sample and non-probability sampling strategy of 40 respondents. This research is a quantitative study whose data collection process uses a questionnaire. The results showed that the Effective Communication Variable was proven to have a significant relationship with Employee Performance. There is an insignificant relationship between Leadership Variables and Employee Performance. Work discipline has an insignificant effect on employee performance. Morale significantly affects employee performance. Implications leaders can improve variables that are still low that can improve employee performance